Periode Perkembangan Darulfunun El-Abbasiyah 1854-2020 - Abdullah A Afifi; Afifi Fauzi Abbas (IDRIS Darulfunun Institute, 2020)
Darulfunun's long journey in the world of education, especially in Islamic education in Indonesia nearly entered two centuries. From it starts, Darulfunun already persevered through varieties of circumstances in serving education for benefiting the society. Darulfunun concern in developing Islamic education already tested in their long journey and innovations that they share with Indonesia modern Islamic education today. Darulfunun established the moderated education concept that combines sciences and religion as one integrated knowledge. In addition, Darulfunun reformed the non-curriculum halaqah education into the classroom education curriculum. In its transformation, the thought and methods promoted by Darulfunun are genuinely become a treasure for education society and Islamic thought in Indonesia. This article aims to outline the development periods of Darulfunun with the specific characteristics of each period. Each period is explored by the important events and changes that make it different from other periods. From the observations, it can be presumed that innovation and development carried out by Darulfunun is a significant effort to adjust to the global challenges and participate in solving problems in society.